Поширеність професійного стресу та синдрому “burnout” серед водіїв - Діордічук, Т.І. (Актуальні проблеми транспортної медицини, 2008)
Проведены исследования уровня профессионального стресса и синдрома «выгорания» у 95 водителей грузовых ав томобилей, осуществляющих междуна родные перевозки. Описаны особенности условий труда этой профессиональной группы. Установлено, что высокий уровень профессионального стресса имеют около 4,4% водителей, у 2,2 % выявлен очень высокий уровень стресса. Синдром «выгорания» не является типичным для представителей этой группы. По результатам исследования определена распространенность профессио
нального стресса и синдрома “выгорания” среди водителей международников, выделены основные жалобы, связанные с трудовой деятельностью, сформирова на группу риска по отношению к профессиональному стрессу и разработаны меры по профилактике его развития. The researches of a level of a professional stress and set of symptoms of “burning out” at 95 drivers of lorries exercising the international transportations are carried out. The features of working conditions of this professional group are described. Fixed, that a high level of a professional stress have about 4,4 % of the
drivers, at 2,2 % the high level of a stress is revealed very much. The set of symptoms of “burning out” is not typical of the representatives of this group. By results of research the prevalence of a professional stress and set of symptoms of “burning out” among the drivers foreign affairs specialists is determined, the basic complaints connected to labour activity are allocated is generated group of risk in relation to a professional stress and the measures on prophylaxis of its development.